SPECIES, HOST RANGE, AND IDENTIFICATION KEY OF WHITEFLIES OF BOGOR AND SURROUNDING AREA - Hidayat, Purnama; Bintoro, Denny; Nurulalia, Lia; Basri, Muhammad (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2018)
Species identification, host range, and identification key of whiteflies of Bogor and surrounding area. Whitefly (Hemiptera: Aleyrodidae) is a group of insects that are small, white, soft-bodied, and easily found on various agricultural crops. Whitefly is a phytophagous insect; some species are important pests in agricultural crops that can cause direct damage and can become vectors of viral diseases. The last few years the damage caused by whitefly in Indonesia has increased. Unfortunately, information about their species and host plants in Indonesia, including in Bogor, is still limited. Kalshoven, in his book entitled Pest of Crops in Indonesia, published in the 1980s reported that there were 9 species of whitefly in Indonesia. The information on the book should be reconfirmed. Therefore, this study was conducted to determine whitefly species and its host plants in Bogor and its surroundings. Whiteflies is identified based on the ?puparia? (the last instar of the nymph) collected from various agricultural plants, ornamental plants, weeds, and forest plants. A total of 35 species of whiteflies were collected from 74 species and 29 families of plants. The collwcted whiteflies consist of four species belong to Subfamily Aleurodicinae and 31 species of Subfamily Aleyrodinae. The most often found whitefly species were Aleurodicus dispersus, A. dugesii, and Bemisia tabaci. A dichotomous identification key of whiteflies was completed based on morphological character of 35 collected species. The number of whitefly species in Bogor and surrounding areas were far exceeded the number of species reported previously by Kalshoven from all regions in Indonesia.